ANALISIS PENERAPAN E-SYSTEM PERPAJAKAN PADA WAJIB PAJAK PRIBADI TERHADAP PELAKSANAAN SELF-ASSESMENT SYSTEM DALAM MEMENUHI KEWAJIBAN PERPAJAKAN - Widjaja, Helen; Siagian, Arthur Jaya Siagian Jaya (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
E-sytem Modernization taxation is using information technology to the esystemis expected to facilitate taxpayers to report tax. With the use of advanced electronic information in Taxation is expected to improve service to the taxpayer, both in terms of quality and time to be more effective. Objective, is to determine the effectiveness of the use of e-taxation system in the form of e-registration,e-spt, e-filing, e-billing affect the fulfillment of tax obligations personal taxpayers. Research methods used in this study is a research approach Explorative. This research was conducted through interviews, observation, and documentation on KPP Pratama Kebayoran Baru Tiga South Jakarta. The results of this study indicate that the e-system on KPP Pratama Kebayoran Baru Tiga effectively and efficiently.